Growth Limitation of Marine Fish by Low Iron Availability in the Open Ocean - Galbraith, Eric D.; Le Mézo, Priscilla; Solanes Hernandez, Gerard; Bianchi, Daniele; Kroodsma, David (Frontiers in Marine Science, 2019)
It is well-established that phytoplankton growth can be limited by the vanishingly low concentrations of dissolved iron found in large areas of the open ocean. However, the availability of iron is not typically considered an important factor in the ecology of marine animals, including fish. Here we compile observations to show that the iron contents of lower trophic level organisms in iron-limited regions can be an order of magnitude less than the iron contents of most fish. Although this shortfall could theoretically be overcome if iron assimilation rates were very high in fish, observations suggest this is not the case, consistent with the high recommended iron contents for mariculture feed. In addition, we highlight two occurrences among fish living in iron-poor regions that would conceivably be beneficial given iron scarcity: the absence of hemoglobin in Antarctic icefish, and the anadromous life history of salmon. Based on these multiple lines of evidence, we suggest that the iron content of lower trophic level organisms can be insufficient to support many fish species throughout their life cycles in iron-poor oceanic regions. We then use a global satellite-based estimate of fishing effort to show that relatively little fishing activity occurs in High Nitrate Low Chlorophyll (HNLC) regions, the most readily-identified iron-poor domains of the ocean, particularly when compared to satellite-based estimates of primary production and the observed mesozooplankton biomass in those waters. The low fishing effort is consistent with a low abundance of epipelagic fish in iron-limited regions, though other factors are likely to contribute as well. Our results imply that the importance of iron nutrition extends well beyond plankton and plays a role in the ecology of large marine animals.